The Emotional Appetite Questionnaire (EMAQ)’s Reliability and Validity and Relationship with Body Mass Index and Emotional Schemas - Baþak Demirel; K. Fatih Yavuz; M. Emrah Karadere; Yasir Þafak; M. Hakan Türkçapar (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: In this study we aimed to implement the reliability and validity analyses of Emotional Appetite Questionnaire (EAQ) in Turkish sample, which has been developed for evaluating relationship between eating behavior and emotion. In addition we aimed to investigate the relationship between EAQ and emotional schemas and body mass index. Method: 196 university students and hospital staff voluntarily included to our study. Participants firstly asked to complete the socio-demographic data form. Turkish form of the EAQ, Eating Attitudes Test (EAT) and the Leahy Emotional Schema Scale (LESS) was given to criteria met participants. To determine the reliability of the scale as required by test-retest method, participants were given a section again after 1 month. Results: Results: For reliability analysis of Turkish version of EAQ (TEAQ); internal consistency, item-total score correlations and test-retest reliability were assessed. TEAQ have a high level of internal consistency and each items in the whole of scale shown to be compatible and complementary. Pearson correlation coefficients were calculated for test-retest reliability analysis of TEAQ and obtained high degree evidence. Significant positive correlations (p< 0.01) determined between negative total scores of TEAQ and BMI scores. In addition significant negative correlations (p< 0.01) determined between positive total scores of TEAQ and BMI scores. Between Leahy Emotional Schema Scale (LESS) sub-dimensions scores and TEAQ sub-dimensions scores, significant negative relationships were obtained (p<0.05, p<0.01). Conclusion: As a result of the present study, DÝA has showed that is a reliable and valid measurement tool for the evaluation of emotional eating in our data sample of Turkey. [JCBPR 2014; 3(3.000): 171-181]